(3GdYfGjI GdQHGfjI aj GdWQjbI GdTYHGfjIs - (3TYHGf Hf eMeO Hf OGhO GdYQTj GdTGaYj, Rjf GdOjf CHh SYjO,J (B828 (3g` s
(3ChdgG (B:s
(3hHYO aGdNW YXje aVdg YfO GdEdg hGdcQGe Ggdg hbO CJi GdMK Ydi JMUjdg hce Odjd LGA aj JaVjdg s
(3BNQgG (B:s
(3hHGdbHhd ddPj LeYJg aj fXegG hddPj hVYJg hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hBdg hSde s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B126s
(3eUOQ GbJfGA GdCUd (B:s
(3djHjG (B- (3ecJHI GdChbGa WQGHdS GdZQH (B(34) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs